KIR Genotypes Impact Progression to Hepatocellular Carcinoma in Patients with Chronic Hepatitis C Infection - Waleed Abdelmaguid; Doha Maher; Mohamed A. S. Kohla; Sameera Ezzat; Inas Moaz; Wael S. Abdel-Mageed; Khalil A. El-Halfawy; Mohamed H. Abdel-Rahman (Livers, 2023)
In Egypt, hepatocellular carcinoma (HCC) is the most prevalent cancer in men and the second most prevalent cancer in women. In addition, Egypt has one of the highest prevalences of hepatitis C infection in the world. The aim of the present work was to study the potential role of the 16 KIR genes in the outcome of individuals with chronic hepatitis C virus (HCV) infection in Egypt. The study was carried out under an IRB-approved protocol. Sequence-Specific-Primer-PCR (SSP-PCR) was used for KIR genotyping of germline DNA extracted from peripheral blood leukocytes or from the non-tumor liver of 83 HCC patients, 100 patients with chronic HCV infection without HCC, and 120 matched healthy controls. Out of the 83 HCC patients, only 7 (8.4%) were treated by interferon and/or interferon Ribavirin combination, while for the remaining patients 50 (60.2%) received no prior HCV therapy and 26 (31.3%) were treated with direct-acting antiviral (DAA). Our results showed that KIR haplotype AA that contains more inhibitory KIR genes and fewer activating genes was observed with a significantly lower frequency in HCC patients (6/83, 7.2%) compared to chronic HCV (27/100, 27.0%) (p = 0.0005, OR = 0.21 [0.08–0.53]) and healthy controls (29/119, 24.4%) (p = 0.001, OR = 0.24 [0.09–0.61]). In addition, the frequency of genotype 6 (G6) which contains all the KIR genes was significantly high in the HCC patients (16/83, 19.3%) compared to chronic HCV (8/100, 8.0%) (p = 0.02, OR = 2.7 [1.11–6.79]) and healthy controls (8/119, 6.7%) (p = 0.006, OR = 3.31 [1.35–8.16]). Activating KIR genes 2DS1 and 3DS1 were significantly higher in HCC patients (48/83, 57.83% and 45/83, 54.22%) compared to the chronic HCV patients (36/100, 36% and 34/100, 34%), p = 0.028, 0.027, respectively. Our results are contrary to a prior work on HCC from patients with HCV who were mostly treated by interferon-based therapies. In conclusion, KIR haplotype AA has an important role in host defense against HCC progression especially in patients treated by DAA, suggesting an important role of the KIR genotype status on the outcome of chronic HCV infection.